Conceptualization of the expansion of the Authority of the Supreme Court as a Dispute Settlement Institution for Authority of State Institutions outside the Constitution - Bakhtiar, Handar Subhandi; Fauzan, Muhammad (Unram Law Review, 2024)
The authority to form state institutions outside the constitution, especially Non-Ministry Government Institutions (LPNK) rests with the President based on Article 4 paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The formation of these state institutions is not limited as the regulation on the number of state ministries which limits the number of ministries to 34 (thirty four). This can create the potential for overlapping authorities and authority disputes between state institutions outside the constitution so that it requires a state institution that can resolve them. Based on this, this study will examine related 1) how to reconstruct the President's authority in forming state institutions outside the constitution; and 2) how to conceptualize the extension of the authority of the Supreme Court as a dispute resolution institution for the authority of state institutions outside the constitution. This study uses a normative juridical method with a statutory approach. The results of the study indicate that the President has the authority to form state institutions outside the constitution through his authority in submitting Draft Laws, forming Government Regulations in Lieu of Laws, and forming Presidential Regulations, in which there are no restrictions. Arrangements for the formation of state institutions outside the constitution must be limited as state ministries in Article 15 of the Law on State Ministries. Then the concept of extending the authority of the Supreme Court as an institution for resolving disputes over the authority of state institutions outside the constitution can be taken from the granting of authority through attribution through Article 24A paragraph (1) of the 1945 Constitution of the Republic of Indonesia. The position of the Supreme Court as a constitutional organ and institution of judicial power is independent from other powers so that it has the potential to become an institution for resolving disputes over the authority of state institutions outside the constitution